Faktor-Faktor yang Mempengaruhi Kebahagiaan pada Istri Pertama dalam Perkawinan Poligami - Suwarti; Arifa, Farah Eza (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Raden Rahmat Malang, 2023)
Marriage is a physical and spiritual bond between a man and a woman as husband and wife with the aim of forming a happy and eternal household based on the One Godhead. Happiness is the satisfaction that is felt in life and is often described to judge decisions that result from the fulfillment of various needs and expectations. Polygamy is a man who has more than one wife. The research aims to determine the description of happiness in the first wife in a polygamous marriage. Focus of this research is on the factors that influence the happiness of polygamous marriages. The participants in this study were 3 participants consisting of NS, AJS, and T. The data were collected using interview and observation methods. The approach method in this study uses a phenomenological study approach with data analysis techniques Interpretative Phenomenological Analysis. The credibility of the data used by researchers using source triangulation. The results of this study are that each participant has a picture of happiness from acceptance, openness, guided by religious teachings, and also communication between partners. This happens because in deciding to be willing to be polygamous, some are due to getting threats by their partners, occur without the knowledge of the partners and some have been agreed upon between the partners. Each participant in this study has a picture of acceptance, openness, guided by religious teachings, communication between various partners, all of which are factors that affect the happiness of polygamous marriages. Another finding from this study is that couples who run polygamous marriages begin with openness, communication between partners goes well, it will be easier to accept the situation in polygamous marriages. Keywords: First Wife, Happiness, Polygamous Marriage.